Leadership Selection and Gender Equity in Principalship: A Cross-National Comparative Study (Pragya Darshan प्रज्ञा दर्शन, 2025)
This comparative study explores principal selection processes and gender dynamics in educational leadership across Nepal, India, China, South Korea, Thailand, and the United States. Employing a qualitative descriptive approach, it integrates a systematic literature review with semi-structured interviews to examine how institutional structures and cultural norms shape leadership pathways. Despite formal mechanisms aimed at merit-based selection, systemic gender biases persist, limiting women’s access to principalship roles.Female leaders, however, consistently demonstrate relational and transformational leadership qualities empathy, collaboration, and inclusivity—that contribute to school improvement and equity. The study highlights the need for gender-responsive selection policies, inclusive leadership development, and supportive institutional cultures. Advancing women in school leadership is not only a matter of equity but a strategic imperative for fostering resilient, innovative, and inclusive education systems.